Why would the parties agree to a ROFR? Deepening on the right of first refusal - Alvarez Calderón, Diego Carrión (2023)
The purpose of this article is to acquaint the reader with the main institutions and characteristics of the right of first option established in a shareholders’ agreement, usually in the scenario of mergers and acquisitions of companies.To this end, the author analyzes the usual restrictions between the parties to prohibit the disposal of shares (and how they differ from the right of first refusal), costs and benefits of establishing this classic clause, alternatives (in some cases less expensive, but also less efficient). Finally, the author explains the innovative ‘commitment to auction’ clause that represents the convergence between the right of first refusal and keeping third party bids open without distorting values.